Morphological and Isokinetic Strength Differences: Bilateral and Ipsilateral Variation by Different Sport Activity - Maly, Tomas; Mala, Lucia; Bujnovsky, David; Hank, Mikulas; Zahalka, Frantisek (Open medicine (Warsaw, Poland), 2019)
BACKGROUND: The purpose of this study was to investigate the morphological and isokinetic strength asymmetry and magnitude in young athletes. METHODS: One hundred and thirty nine male subjects (soccer, floorball, non-athletes) were measured for proportion of muscle mass between upper extremities (BADΔ) and lower extremities (BLDΔ). Moreover, the peak muscle torque of knee extensors (PTE) and flexors (PTF), ipsilateral (H:Q) and bilateral strength ratio (Q:Q, H:H) were measured. RESULTS: We found significant differences in observed parameters with respect to different sport activities (F = 13.02, p = 0.00, η p 2 = 0.80). Higher values of BADΔ were observed in the non-active (0.19 ± 0.11 kg) group compared with soccer players (0.10 ± 0.11 kg). We found a lower value of BLDΔ in floorball players (0.32 ± 0.11 kg) compared with soccer players (0.58 ± 0.27 kg) and non-active boys (0.63 ± 0.28 kg). Results revealed significantly higher PTE in soccer players compared with non-active boys and floorball players and higher Q:Q ratio in soccer players (10.99 ± 7.75%) compared with non-active boys (7.47 ± 5.92%). CONCLUSIONS: This study revealed that there are morphological and strength asymmetries in the observed groups, which may have potential maladaptive effects (e.g. uncompensated overload of extremity) in athletes affected by specific load.
Keywords: Maladaptation; Fitness performance; Isokinetic testing; Body composition